The effects of doping density and temperature on the optoelectronic properties of formamidinium tin triiodide thin films - Milot, R; Klug, M; Davies, C; Wang, Z; Kraus, H; Snaith, H; Johnston, M; Herz, L (Wiley, 2018)
Intrinsic and extrinsic optoelectronic properties are unraveled for formamidinium tin triiodide (FASnI3) thin films, whose background hole doping density was varied through SnF2 addition during film fabrication. Monomolecular charge-carrier recombination exhibits both a dopant-mediated part that grows linearly with hole doping density and remnant contributions that remain under tin-enriched processing conditions. At hole densities near 1020 cm-3, a strong Burstein-Moss effect increases absorption onset energies by ~300meV beyond the band gap energy of undoped FASnI3 (shown to be 1.2 eV at 5 K and 1.35 eV at room temperature). At very high doping densities (1020 cm-3), temperature-dependent measurements indicate that the effective charge-carrier mobility is suppressed through scattering with ionized dopants. Once the background hole concentration is nearer 1019 cm-3 and below, the charge-carrier mobility increases with decreasing temperature according to ~T-1.2, suggesting it is limited mostly by intrinsic interactions with lattice vibrations. For the lowest doping concentration of 7.2´1018 cm^-3, charge-carrier mobilities reach a value of 67 cm2V-1s-1at room temperature and 470 cm2V-1s-1 at 50 K. Intra-excitonic transitions observed in the THz-frequency photoconductivity spectra at 5K reveal an exciton binding energy of only 3.1 meV for FASnI3, in agreement with the low bandgap energy exhibited by this perovskite.